GEOSCIENCES, SPATIAL ANALYSIS AND COLLECTIVE HEALTH: IMPORTANCE OF THE PRACTICE IN RESEARCH PROJECTS FOR GEOGRAPHY STUDENTS - Gonçalves dos Santos, Izani; Pereira da Silva, Isaias; Christine de Sousa Queiroz, Rejane (Journal of Interdisciplinary Debates, 2022)
This article aims to describe experiences from research projects entitled “Children’s calendar incompleteness and racial inequality: birth cohorts (BRISA) in northeastern and southeastern Brazil and“ Spatial analysis of the children’s calendar in São Luís ”that took place from 2016 to 2019 in the Graduate Program in Public Health (PPGSC) of the Federal University of Maranhão. This report consists of the perceptions of the scholarship holders involved and the techniques produced by them that aimed to apply spatial analysis techniques in GIS and geoprocessing to analyze variables that influence childhood vaccination, while maps were produced to discuss the themes covered. Therefore, these experiences are fundamental in educational institutions, especially to broaden the horizons of future specialists in geosciences and geotechnologies, as it allows to take from theory to future technical praxis concomitant with their professions.